Quality of life in young adults with renal transplantation during childwood [A qualidade de vida após o transplante renal na infância] - C. Pinto (2002)
Objective: The aim of this study is to describe and compare the quality of life of young adults that have been submitted to a kidney transplantation during childhood. Population and Methods: This is an exploratory, descriptive and comparative study, including 31 patients with kidney transplant (group 1). Quality of life was assessed with two evaluation scales: SF-36-(general health evaluation tool) and QLI (Specific evaluation tool for this disease). The results obtained were compared with a control group of young healthy adults group 2 (n=62) matched for gender, age, civil status and education. Statistical analysis used Student Test for comparison of means Statistical significance was set at p<0,05. Results: There was statistical significance between group 1 and 2 in all quality life indicators of SF - 36. The correlation of the two scales showed statistical correlation only at mental health level. Conclusions: This results highlighten the variety and complexity of the concept of Quality of Life and emphasise the importance of evaluation of Quality of Life as a means of assessment of health care.